Odpowiedź :
zad. 4
[tex]2(x + 1) + 6 = 4(2 - 3x) - 4 \\ 2x + 2 + 6 = 8 - 12x - 4 \\ 2x + 8 = - 12x + 4 \\ 2x + 12x = 4 - 8 \\ 14x = - 4\\ x = \frac{ -4}{14} = - \frac{2}{7} [/tex]
zad. 5
[tex]a) \frac{1}{5} x + 2 = \frac{1}{3} x - 4 \: \: \: \: \: | \times 15 \\ 3x + 30 = 5x - 60 \\ 3x - 5x = - 60 - 30 \\ - 2x = - 90 \\ x = 45[/tex]
[tex]b) \frac{x + 1}{5} = \frac{x + 7}{6} \: \: \: \: | \times 30 \\ 6(x + 1) = 5(x + 7) \\ 6x + 6 = 5x + 35 \\ 6x - 5x = 35 - 6 \\ x = 29[/tex]
Odpowiedź:
proszę
4.
2(x+1)+6=4(2-3x)-4
2x+2+6=8-12x-4
2x+12x=8-4-2-6
14x=-4 /:14
x= -4/14=-2/7
5.
a) 1/5x+2=1/3x-4
1/5x-1/3x= -4-2
3/15x-5/15x= -6
-2/15x= -6 /:(-2/15)
x= 45
b) (x+1)/5=(x+7)/6 /*30
30(x+1)/5=30(x+7)/6
6(x+1)=5(x+7)
6x+6=5x+35
6x-5x=35-6
x=29
Szczegółowe wyjaśnienie: